A combination of physical activity and computerized brain training improves verbal memory and increases cerebral glucose metabolism in the elderly - Shah, T.; Verdile, Giuseppe; Sohrabi, H.; Campbell, A.; Putland, E.; Cheetham, C.; Dhaliwal, Satvinder; Wienborn, M.; Maruff, P.; Darby, D.; Martins, R. (Nature Publishing Group, 2014)
Physical exercise interventions and cognitive training programs have individually been reported to improve cognition in the healthy elderly population; however, the clinical significance of using a combined approach is currently lacking. This study evaluated whether physical activity (PA), computerized cognitive training and/or a combination of both could improve cognition. In this nonrandomized study, 224 healthy community-dwelling older adults (60–85 years) were assigned to 16 weeks home-based PA (n=64), computerized cognitive stimulation (n=62), a combination of both (combined, n=51) or a control group (n=47). Cognition was assessed using the Rey Auditory Verbal Learning Test, Controlled Oral Word Association Test and the CogState computerized battery at baseline, 8 and 16 weeks post intervention. Physical fitness assessments were performed at all time points. A subset (total n=45) of participants underwent [18F] fluorodeoxyglucose positron emission tomography scans at 16 weeks (post-intervention). One hundred and ninety-one participants completed the study and the data of 172 participants were included in the final analysis. Compared with the control group, the combined group showed improved verbal episodic memory and significantly higher brain glucose metabolism in the left sensorimotor cortex after controlling for age, sex, premorbid IQ, apolipoprotein E (APOE) status and history of head injury. The higher cerebral glucose metabolism in this brain region was positively associated with improved verbal memory seen in the combined group only. Our study provides evidence that a specific combination of physical and mental exercises for 16 weeks can improve cognition and increase cerebral glucose metabolism in cognitively intact healthy older adults.